THE USE OF ROLE PLAY TO IMPROVE SPEAKING SKILL FOR GRADE XI OF SMK SANGKURIANG 2 CIMAHI - Agung Gumelar; Aditya Dwi Sugara (IKIP Siliwangi, 2019)
The qualitative data were analyzed by reducing the data, displaying the data, drawing conclusion and verification. The outcome of the quantitative data is the main score of the test . The validity of the research data was, effect, progression, catalytic, and dialogic validity. The reliability of the research data used three step of triangulation, the first is time triangulation, the second is investigator triangulation, and the last theoretical triangulation, finally we have to used inter-rater reliability. The the pre-test result that the mean score of the grammar in the students’ performance was only 2.0. The vocabulary mean score was 2.5, the perception mean score is 2.7, the fluency mean score was 2.2, and the pronunciation’s mean score was 2.3. Meanwhile, the mean score of the grammar in the students’ performance in the post-test was 3.0. Then, the vocabularies mean score is 3.5, the perception mean score is 3.2. the fluency mean score is 3,0, and the pronunciations mean score is 3.0. Therefore, it is very clear that there were significant improvements on the students’ speaking skill through the use of role play. Therefore, it was very clear that there were significant improvements on the students’ speaking skill through the use of role play. Keywords: improvements, role plays, speaking skill